PENGARUH PEMBELAJARAN DARING PADA DEPRESI, STRES, DAN KECEMASAN MAHASISWA - Maya Primeradama Yanti; Nurul Retno Nurwulan (Jurnal Muara Pendidikan, 2021)
This study aimed to evaluate depression, stress, and anxiety on college students due to the online classes during COVID-19 pandemic using Depression Anxiety Stress Scale (DASS). A total of 106 college students from Sampoerna University with age ranging from 17 to 25 years old participated in this study. The data collection was done using accidental sampling technique by asking students’ consents to participate in this study. Multiple regression analysis was used to measure the factors affecting stress and anxiety on students during the online learning. The results of the study showed that difficulty to enjoy free time and feeling scared for no reason are the causes of the depression, stress, and anxiety on college students